Tuning electronic structure and carrier transport properties through crystal orientation control in two-dimensional Dion-Jacobson phase perovskites - Byunggeol Kim; Jeehong Park; Donghee Kang; Na Eun Jung; Kitae Kim; Hongsun Ryu; Joon Ik Jang; Soohyung Park; Yeonjin Yi (Nano Convergence)
Abstract Two-dimensional halide perovskites are attracting attention due to their structural diversity, improved stability, and enhanced quantum efficiency compared to their three-dimensional counterparts. In particular, Dion-Jacobson (DJ) phase perovskites exhibit superior structural stability compared to Ruddlesden-Popper phase perovskites. The inherent quantum well structure of layered perovskites leads to highly anisotropic charge transport and optical properties. Therefore, controlling the preferred crystal orientation (parallel or perpendicular) is crucial for optimizing device performance. This work presents a rational strategy to control parallel and perpendicular crystal growth in C6N2H16PbI4 (4AMPPbI4)-based DJ phase perovskite thin films. We demonstrate that crystal orientation depends on crystal growth rates, which can be controlled by varying the solvent composition, antisolvent, and annealing temperature. Direct and inverse photoelectron spectroscopy reveals that the electronic structure of 4AMPPbI4, including its work function, ionization energy, and electron affinity, is orientation-dependent. Different orientations significantly affect carrier transport as confirmed by single-carrier devices. This study highlights the critical role of crystal orientation in DJ phase perovskites for designing high-performance optoelectronic devices. Graphical Abstract